2004
DOI: 10.1210/jc.2004-1003
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Levels Are Dependent on Sleep Duration: Relationships with Sympathovagal Balance, Carbohydrate Regulation, Cortisol, and Thyrotropin

Abstract: Sleep plays an important role in energy homeostasis. The present study tests the hypothesis that circulating levels of leptin, a hormone that signals energy balance to the brain, are influenced by sleep duration. We also analyzed associations between leptin and sympathovagal balance, cortisol, TSH, glucose, and insulin under different bedtime conditions. Twenty-four-hour hormonal and glucose profiles were sampled at frequent intervals, and sympathovagal balance was estimated from heart rate variability in 11 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
694
8
57

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 858 publications
(785 citation statements)
references
References 64 publications
26
694
8
57
Order By: Relevance
“…These chronic health conditions could cause short sleep because of discomfort, pain and/or the side effects of medication (Moldofsky, 2001). Some longitudinal data also demonstrate that short sleep could contribute to these conditions (Ayas et al, 2003, Gangwisch et al, 2005, Gangwisch et al, 2006, Patel et al, 2006a, Patel et al, 2006b, Chaput et al, 2008and Shankar et al, 2008 possibly by altering sympathetic nervous system activity, neuroendocrine function and/or hypothalamic-pituitary-adrenal axis activity (Leproult et al, 1997, Spiegel et al, 2004and Van Cauter et al, 2007. However, more research is required to investigate the role of short sleep as a risk factor for chronic disease.…”
Section: Discussionmentioning
confidence: 99%
“…These chronic health conditions could cause short sleep because of discomfort, pain and/or the side effects of medication (Moldofsky, 2001). Some longitudinal data also demonstrate that short sleep could contribute to these conditions (Ayas et al, 2003, Gangwisch et al, 2005, Gangwisch et al, 2006, Patel et al, 2006a, Patel et al, 2006b, Chaput et al, 2008and Shankar et al, 2008 possibly by altering sympathetic nervous system activity, neuroendocrine function and/or hypothalamic-pituitary-adrenal axis activity (Leproult et al, 1997, Spiegel et al, 2004and Van Cauter et al, 2007. However, more research is required to investigate the role of short sleep as a risk factor for chronic disease.…”
Section: Discussionmentioning
confidence: 99%
“…A causative path from sleep and circadian clock system to obesity has been suggested through direct metabolic (see for example Kohsaka et al 17 and Kohsaka and Bass 18 ) and/or hormonal changes with an influence on energy intake. 14,19 More indirect pathways are also plausible, for instance, short or disturbed sleep may cause fatigue leading to restriction of physical activity. Physical inactivity may, in turn, have a negative feed-back effect on sleep.…”
Section: Introductionmentioning
confidence: 99%
“…There is much interest in identifying the physiological basis of these behavioral changes, and studies to date have focused mainly on peripheral endocrine systems (eg, leptin and ghrelin) that regulate feeding in conjunction with energy-balance fluctuations. In some human studies, leptin and ghrelin levels are altered in sleep loss in directions that promote food intake, and rodent studies have shown that sleep curtailment modulates hypothalamic peptides and other systems whose activity tracks these circulating hormones (Barf et al, 2012;Koban et al, 2006;Martins et al, 2010;Spiegel et al, 2004b).…”
Section: Introductionmentioning
confidence: 99%